Recruitment, retention, and engagement of a millennial workforce - Smith, Stephanie, 1985- (Generational differences in higher education and the workplace: leading and teaching millennials and generation Z, 2019)
This book examines how to more successfully recruit, retain and engage millennial employees in various industries for increased job satisfaction and organizational performance. Experts in various areas of organizational communication share insight and best practices for working with millennials.